Determinan Pengangguran Terdidik di Wilayah Perkotaan Perdesaan dan Wilayah Perkotaan Provinsi Kepulauan Riau Tahun 2021 - Nadita Riski Aulia; Lia Yuliana (Seminar Nasional Official Statistics, 2022)
Unemployment is a crucial problem that occurs in Indonesia. Unemployment is dominated by educated unemployment. Province Kepulauan Riau occupies the highest position based on the value of TPT in 2021, which is 9.91 percent. For the last 5 years, the Riau Archipelago has always occupied a position above the national TPT. Generally, unemployment is more prevalent in urban areas than in rural areas, this is due to the large number of people moving from villages to cities which causes high demand for jobs in cities. By using secondary data from Sakernas August 2021, this study aims to determine the variables that affect the characteristics of educated unemployment in the Riau Islands Province in 2021 seen from rural urban areas and urban areas only. The methods used are descriptive analysis and inferential analysis using binary logistic regression. The results of the study show that the variables that are significant in influencing educated unemployment in the Riau Islands in 2021 when viewed from rural urban areas and urban areas only are age, job training and work experience.